Physical Activity of Patients With Chronic Pain Receiving Acceptance and Commitment Therapy or Cognitive Behavioural Therapy. Issue 2 (21st May 2014) - VanBuskirk, Katherine; Roesch, Scott; Afari, Niloofar; Wetherell, Julie Loebach
Abstract : Physical activity is positively related to various indices of quality of life and is found to reduce symptoms in individuals with chronic pain. This manuscript presents findings from a post hoc analysis investigating whether treatment-related improvements from psychological treatment for chronic pain are mediated by changes in physical activity (PA). Secondary analyses sought to determine predictor variables of PA in patients with chronic pain and to determine the relationship between objective and self-report measurements of PA. The effect of psychological treatment on physical activity was assessed using accelerometers in a sample of participants with chronic pain in a randomised controlled trial comparing 8 weeks of acceptance and commitment therapy (ACT) to cognitive behavioural therapy (CBT). Participants wore actigraph accelerometers for 7 consecutive days at baseline, post-treatment, and at 6-month follow-up. Hierarchical linear modelling analyses found that the variance in physical activity was not significantly predicted by time (b = 104.67, p = .92) or treatment modality (b = −1659.34, p = .57). Women had greater increases in physical activity than did men (b = 6804.08, p = .02). Current 'gold standard' psychological treatments for chronic pain were not found to significantly increase physical activity, an important outcome to target in the treatment of physical and mental health. These results suggest that tailored interventions with greater emphasis on exercise may complement psychological treatment for chronic pain. In particular, gender-tailored interventions may capitalise on physical activity differences found between men and women.